[PP.22.13] EVALUATION OF EFFICACY AZILSARTAN MEDOXOMIL ON CENTRAL AORTIC BLOOD PRESSURE AND AMBULATORY BLOOD PRESSURE IN PATIENTS WITH MILD TO MODERATE ESSENTIAL HYPERTENSION. (September 2017) - Dobrokhod, A.; Sirenko, Yu.; Torbas, O.; Granich, V.; Kushnir, S.
Abstract : Objective: This study was aimed to evaluate the effect of azilsartan medoxomil (AZL) on central aortic blood pressure (CAP) and 24-hours blood pressure (BP) in grade 1 and 2 hypertensive patients. Design and method: Thirty nine patients (79% men, all white, mean age – 40 years) with mild to moderate essential hypertension, never treated before, were enrolled. Dose of AZL was gradually increased until maximum 80 mg once-daily. Follow-up of the study amounted to 6 months. CAP measurement (SphygmoCor CVMS, Atcor, Australia) and 24-hours blood pressure monitoring (ABPM, Meditech, Hungary) were measured before treatment and on the last visit. Results: Mean value (mean ± SEM) of baseline 24-hours systolic BP (SBP) was 142 ± 2, 09 mm Hg and 24-hours diastolic BP (DBP) – 85 ± 2, 14 mm Hg, while mean value of CAP was 137 ± 2, 9 mm Hg. At the end of the study mean value of 24-hours SBP was 127.2 ± 1.2 mm Hg, 24-hours DBP – 75 ± 1.8 mm Hg and CAP was 119 ± 2, 1 mm Hg. So decrease from baseline to final CAP, 24-hours SBP and 24-hours DBP were −18, −15 and −10 mm Hg respectively. An outcome of the study shows a significant reduction in both 24-hours SBP and DBP (p < 0.0001) and CAP changes (p < 0.005). Conclusions: Once-daily AZL effectively lowers CAP in adults with mild to moderate essential hypertension and has shown good antihypertensive efficacy according to 24-hours blood pressure monitoring as well.